Effect of Bonding Area on Bond Stress Behavior of GFRP Bars in Concrete - . Fakhruddin; . Kusnadi; Rudy Djamaluddin; Rita Irmawaty; Suharman Hamzah; Luna N. Ngeljaratan (Civil Engineering Journal, 2023)
The application of Glass Fiber Reinforced Polymer (GFRP) bars is suitable for concrete structures that are susceptible to corrosion, owing to their corrosion-resistant characteristics. Therefore, it is feasible to reduce the concrete cover on reinforced concrete beams by utilizing GFRP bars. However, this can reduce the bonding strength between GFRP bars and concrete. Therefore, this study aims to investigate the bonding behavior between GFRP bars and concrete as a preliminary test for structural applications. The bond stress behavior between GFRP bars and concrete was analyzed by 18 pull-out tests. The test specimens comprised GFRP bars with three different variations, namely GFRP bars with concrete cover (GFRP-C), GFRP bars without concrete cover (GFRP-E), and GFRP bars with a complete wrapping of GFRP sheet (GFRP-C-Sheet). The bond stress-slip curve, bond strength, and failure pattern were utilized to analyze the effect of each variation. The research results indicate that the bonding stress between GFRP bars and concrete was strongly influenced by the concrete cover, where the bonding strength decreased by 65%. Nevertheless, the utilization of a complete wrapping GFR) sheet resulted in a 26.4% increase in bonding stress. The present study has identified three distinct modes of failure, including pull-out (GFRP-C), concrete crushing (GFRP-E), and GFRP sheet debonding (GFRP-C-Sheet). Doi: 10.28991/CEJ-SP2023-09-010 Full Text: PDF